2022
DOI: 10.1128/spectrum.02118-22
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of Diverse Sequence Types of Legionella pneumophila by Legiolert Enzymatic-Based Assay and the Development of a Long-Term Storage Protocol

Abstract: Legionnaires’ disease is caused by the bacterium Legionella pneumophila , which can be found in a variety of water systems. When outbreaks of Legionnaires’ disease occur, it is necessary to find the water systems transmitting the bacterium to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…pneumophila clade shared the ancestral allele at this locus with Philadelphia-1. In contrast, all assemblies ( 71 74 ) representing the pascullei , raphaeli, fraseri , and D-7708 ( 71 ) subspecies cluster (comprising 64/302 or 21.2% of analyzed assemblies) contained the derived DnaK M94I allele. The uneven distribution of Legionella subspecies has been proposed to reflect an underlying occupation of separate ecological niches ( 71 ), so we chose to conduct follow-up experiments on the dnaK mutations observed in our heat-adapted lineages.…”
Section: Resultsmentioning
confidence: 95%
“…pneumophila clade shared the ancestral allele at this locus with Philadelphia-1. In contrast, all assemblies ( 71 74 ) representing the pascullei , raphaeli, fraseri , and D-7708 ( 71 ) subspecies cluster (comprising 64/302 or 21.2% of analyzed assemblies) contained the derived DnaK M94I allele. The uneven distribution of Legionella subspecies has been proposed to reflect an underlying occupation of separate ecological niches ( 71 ), so we chose to conduct follow-up experiments on the dnaK mutations observed in our heat-adapted lineages.…”
Section: Resultsmentioning
confidence: 95%
“…This additional step was not strictly necessary and was taken to enable collection of L. pneumophila isolates for sequencing. A recent study (Matthews et al, 2022) found that L. pneumophila isolates can also be obtained directly from the Legiolert ® tray for serotyping and/or storage for a year or more. If ISO Method 11731:2017 is used instead of Legiolert ® , follow-up analyses of positive samples should identify organisms to the species level and serogroup for L. pneumophila isolates.…”
Section: Protocolmentioning
confidence: 99%